Identifikasi mikroplastik pada anadara antiquata di pesisir desa Garassikang kabupaten Jeneponto - Asdar, Muhammad Risqal Pratama; Daud, Anwar; Basir (Institute for Advanced Science, Social, and Sustainable Future, 2024)
Microplastics are small particles <5 mm in size that come from plastic waste. The large amount of plastic waste produced every day, most of which is thrown into the sea, means that the presence of microplastics continues to increase and is widespread almost throughout the sea surface, including Jeneponto Regency. This is very risky for contamination of feather shellfish which are often consumed by local people, so it is very dangerous for health. Therefore, it is necessary to identify microplastics in feather shellfish in Garassikang Village. Aim to determine the characteristics of microplastics in feather clams found on the coast of Garassikang Village, Jeneponto Regency in 2023. This type of quantitative research uses a descriptive approach with laboratory tests. The population is all edible shellfish obtained directly in the coastal waters of Garassikang Village, Jeneponto Regency, with a total sample of 15 feather shellfish obtained using a purposive sampling technique. The average abundance of microplastics in feather clams was 512.53 particles/kg with a microplastic size of 0.027 mm - 6,800 mm. There are 2 types of microplastics found, namely fibers and fragments, and there are 3 types of microplastic colors, namely blue, red and transparent. There are microplastics in shellfish found on the coast of Garassikang village. Of the 15 shellfish samples, 12 shellfish contained microplastics, this needs to be investigated in more depth regarding how dangerous exposure to microplastics is to human health using the FTIR test.